REVIEW DEVELOPMENT STATUS AND FUTURE TRENDS OF MICRO UAVS. - Haoyang, Li (Science-based technologies, 2024)
The article "Development Status and Future Trends of Micro UAVs" presents an in-depth examination of the evolution and prospective advancements in micro unmanned aerial vehicles (micro-UAVs). The introduction traces the origin of micro-UAVs to the DARPA's "Micro air vehicles" program, focusing on their compact size, lightweight, and multifunctional capabilities for tasks like battlefield intelligence and situational surveillance​​. The development status section outlines the progression from early models like the "MSI," "Black widow," "Nano Hummingbird," and "Black hornet" to more recent iterations such as the "Black hornet3," "Meta Fly," and "Robo Bee X-Wing." These models demonstrate significant advances in micro-nano technology and system integration, enhancing their application in diverse environments​​. The article also highlights typical research projects, underscoring the growing emphasis on artificial intelligence and micro-UAV clusters. It mentions significant initiatives like the "Grey Partridge" UAV swarm project, the CICADA project, and the Fast Lightweight Autonomous Project (FLA), which focus on cluster research, indoor and outdoor navigation, and obstacle avoidance​​. Key technological aspects are discussed next, including the miniaturization of onboard equipment, low Reynolds number aerodynamic design, and autonomous navigation and obstacle avoidance in complex environments. The article elaborates on how the small size and high maneuverability of micro-UAVs are suitable for intelligence search in restricted spaces, and how their design is adapting to low Reynolds number aerodynamics and complex navigation requirements​​. The future trends section predicts further advancements in the integration and generalization of onboard equipment, cross-media aerodynamic design, and increased intelligence of micro-UAVs. It anticipates the development of more intelligent control methods, including biometric technologies, to enhance the functionality of micro-UAVs in complex, dynamic environments​​. In conclusion, the article asserts that micro-UAVs are increasingly suitable for varied applications, especially in indoor or urban reconnaissance. However, it points out that there is room for improvement in integrating and generalizing onboard equipment and developing more versatile and adaptive autonomous navigation technologies. The article posits that as micro-UAVs become more intelligent and adaptable, they will play a crucial role in future information warfare.